(untitled) (BSAA arte, 2020)
The church of San Miguel de Reoyo in Peñafiel (Valladolid, Spain) has a Romanesque apse dating from the 12th century that still preserves badly damaged Gothic wall paintings representing the Last Judgement. Studying their composition, iconography, theme and style in their artistic context, we propose a reconstruction of the ensemble and we suggest that their author maybe adapted the theme in order to present Christ both as judge and Saviour, combining influences from both the Italian Trecento and the international style. We propose that this mural was approximately created in the second quarter of the 15th century, at a time when Peñafiel was a duchy property of the Aragonese branch of the House of Trastámara.